Akad Murabahah dan Inklusivitas Ekonomi Halal: Studi pada Pembiayaan Syariah Baitul Tamwil Hidayatullah Makassar - Jamaluddin Jamaluddin; Hasanna Lawang; Andi Sumardin; Syamsinar Syamsinar; Elena Mariantika (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
Murabahah contracts play an important role in opening access to financing for groups that have long been marginalized by the conventional banking system. Thus, this contract not only strengthens the halal ecosystem but also provides religious legitimacy and a sense of security for small business actors. Nevertheless, several obstacles such as low financial literacy, high operational costs, and weak financial records among microenterprises remain challenges that need to be addressed. Driving factors such as regulatory support for sharia, the rise of Islamic financial literacy, and public trust in micro-sharia institutions reinforce the sustainability of murabahah practices. The strategies implemented by BTH Makassar ranging from member segmentation, integration of social funds, business mentoring, digitalization of services, to regular monitoring demonstrate an orientation that is not only financial but also social. Murabahah at BTH Makassar emerges as a financing model capable of integrating religious, social, and economic aspects. It becomes an effective instrument of halal financial inclusion, strengthening the competitiveness of microenterprises while simultaneously building a sharia economic ecosystem that is more just, sustainable, and resilient.